Assessment Model of the Architecture of the Aerospace Embedded Computer. (2015) - Han, Wei; Bai, Xiaoying; Xie, Jianchun
Abstract: Typical aerospace embedded computers have many characters in common, especially in the aspect of the design of computer architecture. To evaluate this category of computers, 3 typical aerospace embedded computers were sampled and their characters of architecture and common technology were analyzed. Eight characters of architecture were concluded, and three evaluation dimensions were proposed. A basic guideline and a practical reference value or design were attached to each architecture character. The relationship was analyzed among the final assessment result, the evaluation dimensions and the architecture characters. Any aerospace embedded computer can be scored according to the assessment model for various estimate requirements. The evaluating method and progress were illustrated through one kind of advanced aerospace embedded computer's evaluation case. The case indicates that the assessment model is clear, effective and practical. It can provide some guidance for the design and performance analysis of aerospace embedded computers.